Cool-season annual pastures with clovers to supplement wintering beef cows nursing calves - Gunter, Stacey A (BioMed Central, 2012)
In December of 3 years, 87 beef cows with nursing calves (594 ± 9.8 kg; calving season, September to November) at side were stratified by body condition score, body weight, cow age, and calf gender and divided randomly into 6 groups assigned to 1 of 6 cool-season annual pastures (0.45 ha/cow) that had been interseeded into a dormant common bermudagrass (Cynodon dactylon [L.] Pers.)/bahiagrass (Paspalum notatum Flugge) sod. Pastures contained 1 of the following 3 seeding mixtures (2 pastures/mixture): 1) wheat (Triticum aestivum L.) and ryegrass (Lolium multiflorum Lam., WRG), 2) wheat and ryegrass plus red clover (Trifolium pretense L., WRR), or 3) wheat and ryegrass plus white (Trifolium repens L.) and crimson clovers (Trifolium incarnatum L., WRW). All groups had ad libitum access to grass hay (12% crude protein; 58% total digestible nutrients). The second week in December, cow estrous cycles were synchronized and artificially inseminated. In late December, a bull was placed with each group for 60-d. Data were analyzed with an analysis of variance using a mixed model containing treatment as the fixed effect and year as the random effect. Body weight and condition scores did not differ (P ≥ 0.27) among cows between February and June. Calf birth weights or average daily gain did not differ (P ≥ 0.17) among treatments; however, calves grazing pastures with clovers did tend (P = 0.06) to weigh more than calves grazing grass only. Weaning weight per cow exposed to a bull was greater (P = 0.02) for WRR and WRW than WRG. Cows grazing winter-annual pastures containing clovers tended to wean more calf body weight per cow exposed to a bull than cows grazing the grass only pastures.